PERANCANGAN SISTEM ARSIP SURAT JALAN BERBASIS WEB DI CV SAPI NUSANTARA JAYA - adminjfik adminjfik; Abdurrahman Wibisono Mila; Hasnan Afif Mila (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2022)
CV. Sapi Nusantara Jaya is a joint business entity of members of the cattle and beef cattle fattening business and beef cattle engaged in the feedlot sector. In the process of shipping goods, of course, there is evidence of the issuance of goods in the form of travel documents. This travel document is something that must be included in the process of sending goods so that things do not happen that can harm one or both parties. At CV.Sapi Nusantara Jaya currently still using the conventional way of working. That is still using handwriting and still using forms made of paper, which are likely to be damaged or lost tend to be more vulnerable. The author will do the design of the document processing system on the CV. Sapi Nusantara Jaya starts with proof of delivery of goods (goods have been received). This system is designed using PHP (Hypertext Preprocessor) as the programming language and MySQL (My Structured Query Language) as the database, using the SDLC (Sequencial Development Life Cycle) method. It is hoped that this system will maximize admin staff so that the delivery of information and data collection can run effectively. The result of this research is that the design of the document archive is built using the PHP programming language and the MySQL database can make it easier to carry out the data collection process and computerization process.